2017
DOI: 10.1089/pho.2016.4180
|View full text |Cite
|
Sign up to set email alerts
|

Scar Remodeling with the Association of Monopolar Capacitive Radiofrequency, Electric Stimulation, and Negative Pressure

Abstract: Objective: A study was established to objectively assess the effects of low-intensity electromagnetic and electric stimulation plus negative pressure on mature scars. Background: Radiofrequency plus negative pressure therapy demonstrated a favorable reorganization and regeneration of the collagen and elastic fibers and was proposed for the treatment of cellulitis and skin stretch marks. Methods: Twenty-six mature scars in 20 Caucasian patients (15 females and 5 males) were enrolled in the study. The treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In the literature there are not many analyses relating to this technique for the treatment of scars, given that it was recently introduced. In the two works that describe it [ 46 , 74 ], for ethical reasons, no invasive analyzes (e.g., biopsy analysis) were performed to evaluate the effectiveness of the method. The outcomes of the various treatments were evaluated by non-invasive measurements and were considered satisfactory in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are not many analyses relating to this technique for the treatment of scars, given that it was recently introduced. In the two works that describe it [ 46 , 74 ], for ethical reasons, no invasive analyzes (e.g., biopsy analysis) were performed to evaluate the effectiveness of the method. The outcomes of the various treatments were evaluated by non-invasive measurements and were considered satisfactory in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…The vacuotherapy or vacuum massage applied to the skin leads to mechanical stress on the biological structures that make them up 22 . It is thought that the combination of interventions with vacuum massage can produce an impact on the collagen found in scar tissue and elastic fiber remodeling 23 . However, different from other studies, in this study, with only one application of the intervention, no significant increase was noted for distensibility of both the normal and skin graft for either combination therapy, TUV and TPV 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors believe that the lipoaspirate provides a kind of scaffold around the ulcer that can behave as a biological matrix for cell migration 1,18‐21 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this set of cells and growth factors up‐regulate the ki‐67 pathway in the wound, in order to promote the cellular proliferation 33,35,36 . These evidences suggested that injection of filtered fat graft improves wound healing, but the correlation with pain reduction is less clear 18,19,37‐39 …”
Section: Discussionmentioning
confidence: 99%